(untitled) (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the journal "SALUD, ARTE y CUIDADO" (ISSN: 1690-8414), a means of open access, refereed and indexed scientific dissemination, attached to the Dean of Health Sciences of the University Centroccidental Lisandro Alvarado (UCLA), Venezuela, oriented to the dissemination of the scientific work of Nursing and other Health Sciences related to its philosophy of human care. Founded in 2008 and published biannually, SAC is indexed and cataloged in Emerging Sources Citation Index , Imbiomed, Dialnet, Revencyt, Cabi, Geneva Fundation, Nursing: Free Medical Journal and Technological Information Center of Chile.